Hydration Influence on the Autonomic Recovery of the Coronary Diseases Patient: Geometric Indices Analysis - França da Silva, Anne Kastelianne [UNESP]; Santos, Lorena Altafin [UNESP]; Laurino, Maria Júlia Lopez [UNESP]; Vanzella, Laís Manata [UNESP]; Ribeiro, Felipe [UNESP]; Rozan, Gustavo Bochini; Vanderlei, Luiz Carlos Marques [UNESP] (Taylor & Francis, 2020)
Purpose: To evaluate the recovery period of autonomic modulation, through geometric indices of heart rate variability (HRV), on coronary artery disease (CAD) patients submitted to a cardiovascular rehabilitation session (CR), associated with hydration. Methods: Thirty male participants of a CR program, diagnosed with CAD were submitted to the control (CP) and hydration protocol (HP) characterized by a CR session. Only during HP were the participants given 8 equal portions of water. The water amount was determined through the hydric loss measured at the CP. During the protocols, the heart rate was measured beat-by-beat at rest (5–10 minutes[M1]) and at recovery (0–5 minutes [M2], 5–10 minutes [M3], 15–20 minutes [M4], 25–30 minutes [M5], 40–45 minutes [M6], 55–60 minutes [M7]) for the HRV analysis, performed by the geometric indices: TINN, RRTRI, SD1, SD2 and SD1/SD2 ratio. Results: Statistically significant differences were observed between the protocols (SD1, pvalue  = 0.022), moments (TINN, pvalue  = 0.001; SD1, pvalue  = 0.019; SD2, pvalue  = 0.001; SD1/SD2, pvalue  = 0.001) and moments vs. protocol interaction (SD1, pvalue  = 0.019). The SD1 index pointed to acceleration of parasympathetic recovery in the first minutes after exercising (HP recovery after M3 [86.07 ± 32.31%] vs. CP recovery after M5[86.43 ± 24.56]) and increase in global variability (TINN—HP remained increased in longer, until M5 (M1 83.10 ± 55.76 ms to M5 116.82 ± 67.54 ms) vs. CP that remained increased for a short time, until M2 (M1 77.93 ± 68.56 ms to M2 134.82 ± 56.08 ms). Conclusions: In CAD patients, hydration promoted a more efficient recovery on parasympathetic autonomic modulation and increased the global HRV in the recovery period.
Keywords: Autonomic nervous system; cardiac rehabilitation and coronary artery disease; hydration